Screening of filamentous fungi for production of myrosinase - Rakariyatham N. (2014)
Aspergillus sp. NR46F13, isolated from soil via sinigrin-barium sulphate agar technique, was tested for myrosinase production. The fungus degraded glucosinate and produced 3.19 U mL-1 of myrosinase after 48h cultivation. due to the high myrosinase production, this new isolate is a potential candidate for industrial applications.